An Appraisal of the Capacity of the Asante Akim South District Assembly in Managing Plan Implementation - Kwarteng, Frimpong (2011)
A Thesis submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master of Science, 2008